2016
DOI: 10.1177/2150135115623284
|View full text |Cite
|
Sign up to set email alerts
|

Well-Being and Agency in Parents of Children With Congenital Heart Disease

Abstract: Children's surgery has a positive effect on parent's hopelessness, but it does not have any impact on their well-being nor agency. Parents of children with CHD have a decreased well-being compared to parents of healthy children but have a similar level of agency. Socioeconomic level and gender may influence this association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 29 publications
(43 reference statements)
1
10
0
1
Order By: Relevance
“…On the other hand, they had a similar level of agency (a concept from developmental studies defined as “the ability to act on behalf of what you value and have a reason to value”) (23). Their children’s surgery significantly decreased parental feelings of hopelessness, but had no influence on their well-being or agency.…”
Section: Parental Mental Health Problems After Child’s Cardiac Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, they had a similar level of agency (a concept from developmental studies defined as “the ability to act on behalf of what you value and have a reason to value”) (23). Their children’s surgery significantly decreased parental feelings of hopelessness, but had no influence on their well-being or agency.…”
Section: Parental Mental Health Problems After Child’s Cardiac Surgerymentioning
confidence: 99%
“…Limitations of reviewed studies include, e.g., small sample size or use of non-standardized instruments (23), underestimation of ASD (21), assessment of mental health symptoms “only,” and not of specific psychiatric diagnoses (1315, 17, 20, 21, 23). …”
Section: Parental Mental Health Problems After Child’s Cardiac Surgerymentioning
confidence: 99%
“…These socioeconomic data were analyzed independently and also transformed into a dichotomous variable (poverty) following the multidimensional poverty approach proposed by Aplablaza for the Chilean population [32]. This account has been used in a similar study [33].…”
Section: Plos Onementioning
confidence: 99%
“…Lower scores on mental well-being, as measured by the General Health Questionnaire, were found to be significantly correlated with poverty in parents with a child undergoing cardiac surgery. 39 Another study examined parental stress levels in a paediatric cardiac ICU and step-down unit and found that parental stress scores were negatively correlated with poverty level and that foreign-born mothers had significantly higher stress during their child's hospitalisation. 16 They concluded that poverty, place of birth, and citizenship may all play a role in predicting parental stress levels.…”
Section: Socio-economic Status and Social Statusmentioning
confidence: 99%